Estudo da incorporação de resíduo industrial de caulim em compósitos de matriz polimérica - TAVARES, Jamylle Feitosa de Souza (2021)
The increasing search for materials with specific properties led researchers to show a greater interest in the area of composite materials. Industrial wastes that often are disposed inadequately have been widely used as fillers for these materials. The present work aims to analyze the physical, mechanical and flame resistance properties of polymeric composites reinforced with kaolin residue. These composite materials were produced with isophthalic polyester matrix and fresh and calcined kaolin residue, with mass fractions varying from 5% and 10% of residue. The specimens were made using the hand lay-up method (manual) in metallic mold. Physical tests of water absorption, apparent porosity and apparent specific mass, tensile and flammability tests were carried out according to the standards ASTM D 570, ASTM D 2734, ASTM D 792, ASTM D-3039 and ASTM D 635, respectively. According to the results obtained in the physical tests, the composites showed an increase in AA, PA and MEA compared to full resin. Regarding the tensile test, the RCI-10 composite showed an increase of 12.18% compared to full resin, with a limit of tensile strength of 21.92 MPa. In the flammability test, the composites showed results much lower than those required by the standards. Concerning CONTRAN, the RCI-5 and RCI-10 composites reduced the propagation rate by 77.42% and 76.15%, respectively. And in relation to what determines ASTM D 635, composites showed a decrease in the rate of 43.55% and 40.37%, respectively. The composites did not show significant variations in the flame propagation rate in relation to the full resin. In general, the research carried out showed viable results, considering the incorporation of an industrial waste as a mineral load, it is important to emphasize that the reuse of this waste contributes to the reduction of the environmental impacts generated in its storage process and also reduces the cost of the final product, considering that part of the volume of the polymer is being replaced by a material of lesser value.